Analisis dan Perancangan Tool Aplikasi Penerjemah Bahasa Inggris Ke Dalam Bahasa Indonesia - Supriyanto Karya (Jurnal Informatika dan Bisnis, 2013)
Along with the development of information technology in today's era, making a growing number of emerging new applications, especially in cellular phones. The use of cellular phones besides as a communication media can also be used as a media of learning, such as application translator. Application translator can be tools of learning a language, such as application translator English to Indonesian. The purpose of this research is allow user to be able to translate English into Indonesian on mobile easily. Translator application on this research is developed using the Java programming language (especially J2ME) because of its advantages that can be run on various operating systems and its open source that can be easily developed and distributed. The result of this research is the application of Java-based translator who can translate English sentence into Indonesian sentence. The application can be accessed using a mobile phone with an internet connection. The application has a spelling check feature which can check the wrong word and provide alternative word that approach word of input. The conclusion of this research is translator application can translate sentence in daily conversation quite well with the corresponding translation sentence structure and close to its original meaning and created for support the education and general knowledge.